Molecular Packing in Network-Forming Collagens - Carlo Knupp; John M. Squire (The Scientific World Journal)
Collagen is the most abundant protein among vertebrates and occurs in virtually all multicellular animals. Collagen molecules are classified into 21 different types and differ in their sequence, weight, structure, and function, but they can be broadly subdivided into families. Type IV, VI, VIII, X, and dogfish egg case collagens belong to the network-forming family. Here, we summarise what is known about the way these collagen molecules pack to form networks. In addition the main structural characteristics of the network-forming collagens are compared and discussed.